KESENIAN RONGGENG GROUP SENANDUNG RINDU DI KECAMATAN GUNUANG TULEH KABUPATEN PASAMAN BARAT - Delmalia, Delmalia (Humanus, 2015)
The purpose of the research is to reveal and explain about the matters of Ronggeng performance as a traditional art in Muaro Kiawai village. As a traditional art, Ronggeng now is in endangered due to the declining number of its presentations. This study is qualitative, where data is collected by observation, interviews, and documentation. The research informants were the actors who are involved in Ronggeng art, the ethnic group elites, and the society. The research instruments were the researcher, helped by recording instrument. The data was analyzed using Miles and Huberman model. The study finds that Ronggeng is formed by two type arts; dance and music. Ronggeng is marginalized by the society, because it does not adapt with the current changes and civilization. Therefore, most Ronggeng artists establish Senandung Rindu group in an effort to save Ronggeng from extinction. In the end, the effort contributes to the preservation and sustainability of the existence and activities of Ronggeng in Muaro Kiawai.